Configuração e atribuições do Conselho Tutelar e sua expressão na realidade Pontagrossense - Gebeluka, Rosmeri Aparecida Dalazoana (2008)
The study analyses the setting and the attributes of the Tutelary Council in the context of the democratic state of law and its expression in the reality of Ponta Grossa PR. It discusses the attributes of the Tutelary Council in the Public Political context of child and teenager protection. It approaches the importance of the creation of the children and teenager rights council in Brazil, as a mechanism of participation and social control, implemented as of the decade of 1990, and necessarily created before the Tutelary Councils. It apprehends the different interpretations of the function and attributes of the Tutelary Council by the research participators: Tutelary Councils, Users and the Municipal Social Assistance Secretary, during 2007. The Tutelary Council is an organism of public executive character, created by the state to represent the interests of the civil society in the area of children and teenagers. It is of educated, permanent, autonomous, and not jurisdictional nature, and it is also in charge of inspecting the fulfillment of the children and teenagers rights. It acts based on the Child and Teenager Statute, whenever there is a violation of a child or a teenager for action or omission of the society or the state, by lack, omission or abuse of the family and due to their own behavior, applying counter measures according to its attributions.